Congenital anomalies in children of mothers taking antiepileptic drugs with and without periconceptional high dose folic acid use: a population-based cohort study - Ban, Lu; Fleming, Kate M.; Doyle, Pat; Smeeth, Liam; Hubbard, Richard B.; Fiaschi, Linda; Tata, Laila J. (Public Library of Science, 2015)
BACKGROUND: Antenatal antiepileptic drug (AED) use has been found to be associated with increased major congenital anomaly (CA) risks. However whether such AED-associated risks were different according to periconceptional high dose (5mg daily) folic acid supplementation is still unclear.